The physiological demands of hitting and running in tennis on different surfaces - Fernandez-Fernandez, J.; Kinner, V.; Ferrauti, A. (The Journal of Strength and Conditioning Research, 2010)
The aim of the study was to examine how the training surface (i.e., clay or carpet) affects the characteristics (i.e., ball velocity, running pressure, running volume, and physiological responses) of a tennis training session. Ten competitive healthy and nationally ranked male tennis players (mean ± SD: age 24.2 ± 1.7 years, weight 81.4 ± 7.6 kg, height 1.88 ± 0.05 m, body mass index 23.1 ± 1.8) participated in a maximal treadmill test and a field test (e.g., an on-court tennis training session, which consisted of 4 exercises). Subjects' oxygen uptake (Vo2) and heart rate (HR) were recorded by portable analyzers, and the ball velocity was measured using a radar gun during the training sessions. We did not find any significant influence of the court surface on any of the variables analyzed under the standardized exercise conditions of the study, as suggested in previous studies conducted under match-play conditions. Moreover, data showed significant differences between maximal forehand and backhand stroke velocities, the forehand stroke being significantly faster (p = 0.01) and more energy demanding on both playing surfaces (clay: 122.0 ± 9.1 vs. 111.1 ± 7.5; carpet: 120.4 ± 6.0 vs 111.5 ± 7.0 km/h). Comparing the same stroke on the same court surface, but at different stroke velocities, we found significant differences (p < 0.05) in all the physiological measurements (e.g., HR, %HRmax; VO2; %VO2), which significantly increased with hitting velocity.